2016
DOI: 10.4236/aim.2016.62011
|View full text |Cite
|
Sign up to set email alerts
|

Biological Control of <i>Erwinia carotovora</i> ssp. <i>carotovora</i> by <i>Streptomyces</i> Species

Abstract: Ten isolates of Erwinia carotovora ssp. carotovora (Ecc) were isolated from infected potato tubers of Picasso, Sante, and Nevskiy varieties collected from different regions in Kyrgyzstan. Isolates were identified as Erwinia carotovora ssp. carotovora (Ecc) by standard bacteriological techniques and pathogenicity tests on tubers and also by PCR analyses. Tests on the pathogenicity of E. carotovora ssp. carotovora (Ecc) strains to host plants by artificial inoculation have shown a high sensibility of the Picasso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 22 publications
0
12
0
6
Order By: Relevance
“…Whereas, maximum time taken for complete rotting of carrot was 5 and 7 days by Ipp 6 Igp 9, and Ien 11 , (Table 3). Rotting in carrot was slow and complete rotting was observed after 14 days after inoculation (Schillingford, 1974;Doolotkeldieva et al, 2016).…”
Section: Pathogenicity and Virulence Testmentioning
confidence: 99%
“…Whereas, maximum time taken for complete rotting of carrot was 5 and 7 days by Ipp 6 Igp 9, and Ien 11 , (Table 3). Rotting in carrot was slow and complete rotting was observed after 14 days after inoculation (Schillingford, 1974;Doolotkeldieva et al, 2016).…”
Section: Pathogenicity and Virulence Testmentioning
confidence: 99%
“…These bacteria cause a number of serious plant diseases e.g., canker, necrotic spots, bacterial wilt, rot diseases and lesions in number of crop plants e.g., tomato, pepper, egg plant and citrus. These bacteria have been difficult to control by synthetic pesticides (Doolotkeldieva et al 2016). So, the present study was undertaken to evaluate bioactivities of constituents of A. bisporus partitioned through organic solvents like n-hexane, chloroform and ethyl acetate.…”
Section: Introductionmentioning
confidence: 99%
“…These strains will be old, so its effect will slow down, suggesting that there were other mechanisms that interfered in the biocontrol like competition for iron traces through siderophore production or the ability of some bacterial isolates to activate defense systems in the host plant (Ait Bahadou et al 2018). Doolotkeldieva et al (2016) indicated that the presence or the absence of the disease and its degree was closely related to the concentration of the antagonist. If the concentration decreased, there will be the onset of the disease with an increasing degree.…”
Section: Discussionmentioning
confidence: 99%
“…From literature, fungi and bacteria antibiotics production, phytohormones release (auxins, gibberellins, cytokinins, and ethylene) from Streptomyces diastatochromogenes sk-6, S. graminearus strains, and Trichoderma lignorum, can decrease the virulence of P. carotovorum strain, with a degree differed from one antagonist strain to another, or in dose strain-dependent manner (Doolotkeldieva et al 2016).…”
Section: Discussionmentioning
confidence: 99%